TUJUH KETRAMPILAN DASARUNTUK MEMAHAMI TEKS BERBAHASA INGGRIS UNTUK PEMULA: STUDI KASUS MATA KULIAHBAHASA INGGRIS 1 (ESP) - Setiarini, Riskia (Jurnal Pengembangan Pendidikan, 2011)
Abstract. Non English Departmentstudents find it difficult to understand an English text. Therefore, to answerthe need of those students, ESP is carried out for them. To make themunderstand what a text is about, English sentence patterns in terms of Kernelsentence patterns are introduced to them during the ESP course. However, thisteaching seems not working well. A solution is offered, dealing with sevenskills covering the introduction of parts of speech, phrases, kinds of clauses,subject and finite verbs, and main idea. With lots of drilling on those skills,students realize that they help them much in the text understanding. Keywords: subjects, finite verbs, non finiteverbs, main clauses, sub clauses, main idea